Educational Skills In Choosing Learning Strategies In The Pandemic Case Study In MTs. Miftahul Huda Bulung Kulon, Jekulo, Kudus - Syaroful Anam , Mohammad; Az Zafi, Ashif (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2019)
This study aims to analyze the skills of educators in choosing learning strategies during pandemic case studies at MTs Miftahul Huda. The subjects in this study were learning media used by teachers in the online learning process, namely What's App Group, Zoom Meeting, Learning Videos; and (3) the implementation of learning carried out by the teacher includes lesson planning by making online lesson plans, implementing online learning using voice notes, zooming meetings, as well as the What's App Group; carry out learning evaluations. The conclusion in this study is that the teacher's learning strategy has been implemented using a variety of technological media which are used to achieve learning objectives under the applicable curriculum.